The Influence of Technical, Economic, and Social Factors on the Success of Native Chicken Farming with the Moderating Role of Good Farming Practices in Fakfak Regency - Piet Richard Notanubun; Andoyo Supriyantono; Elfira Karine Suawa (Jurnal Agrosci, 2026)
Background. This study examines the success of native chicken farming in Fakfak Regency, which remains an important livelihood activity but faces various technical and institutional constraints. Aims. The study aims to analyze the influence of technical, economic, and social factors on farming success, as well as to assess the moderating role of Good Farming Practices (GFP). Methods. A mixed-method approach was applied, combining quantitative and qualitative analyses. Data were collected through surveys and in-depth interviews with smallholder farmers. Quantitative data were analyzed using multiple linear regression and moderation analysis, while qualitative data were used to enrich the interpretation of findings. Result. The results indicate that technical factors, such as feeding management and disease control, have the most dominant influence on farming success, followed by economic and social factors. The GFP index significantly strengthens the relationship between these production factors and business outcomes, suggesting that better farming practices enhance overall performance. Conclusion. Qualitative findings reveal persistent challenges, including limited feed availability, weak institutional support, and low adoption of improved technologies. In conclusion, strengthening technical management and promoting GFP implementation are critical for improving productivity. Implementation. The study implies that policy interventions and extension services should focus on capacity building and sustainable farming practices to support smallholder farmers.